AIP Conference Proceedings 2009
DOI: 10.1063/1.3251237
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying and enforcing two-dimensional symmetries in scanning probe microscopy images

Abstract: The overall performance and correctness of the calibration of all kinds of traditional scanning probe microscopes can be assessed in a fully quantitative way by means of "crystallographic" processing of their twodimensional (2D) images from samples with 2D periodic (and preferably highly symmetric) features. This is because crystallographic image processing results in two residual indices that quantify by how much the symmetry in a corresponding scanning probe microscopy image deviates from the symmetries of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 13 publications
(25 reference statements)
1
17
0
Order By: Relevance
“…Our earlier study of regular arrays of F 16 CoPc molecules on Ag (110) revealed somewhat more densely packed domains that possessed only plane group p2 [7]. We also note that two densely packed oblique lattice domains and a more loosely packed domain with a rectangular (pseudosquare) lattice were described in ref.…”
Section: Copc Molecule Array On Silver (111)supporting
confidence: 66%
See 1 more Smart Citation
“…Our earlier study of regular arrays of F 16 CoPc molecules on Ag (110) revealed somewhat more densely packed domains that possessed only plane group p2 [7]. We also note that two densely packed oblique lattice domains and a more loosely packed domain with a rectangular (pseudosquare) lattice were described in ref.…”
Section: Copc Molecule Array On Silver (111)supporting
confidence: 66%
“…Our earlier results of CIP of STM data of 2D periodic arrays of phthalocyanines are summarized in refs. [7,8]. Reference [9] is available in open access on the Internet and gives a comprehensive introduction to CIP for Scanning Probe Microscopy (SPM).…”
Section: Introductionmentioning
confidence: 99%
“…Better "symmetrizations" of noisy 2D periodic images have always been the desired outcome of the standard crystallographic image processing method that is used by the 2D crystallography, transmission electron microscopy, and scanning probe microscopy communities [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and works in Fourier space. These symmetrizations combine the noiseremoval feature of traditional Fourier filtering with the crystallographic averaging over all asymmetric units in the whole image, have been utilized for over 50 years, and contributed to the Nobel Prize in Chemistry to Sir Aaron Klug 8 in the year 1982.…”
Section: Analytical Plane Symmetry Group Classifications In 2dmentioning
confidence: 99%
“…The derived mathematical framework is nowadays utilized for the classification of (i) highly magnified but necessarily noisy experimental images from crystals that are sufficiently thin (so that quasi-kinematic imaging conditions prevail) and crystal surfaces as recorded with modern transmission electron and scanning probe microscopes [7][8][9][10][11][12][13][14][15][16][17][18], of (ii) both perfectly 2D periodic and noisy synthetic images [18][19][20][21][22][23][24][25][26], as well as of (iii) more or less 2D periodic images from rugs, windows, a honeycomb, both a tiled floor and wall, metal gates, a metallic anti-skid surface [26], industrially manufactured wallpapers [27][28][29], textiles, and decorative ceramic tiles [29][30][31][32][33], medieval Islamic building ornaments [34], and images of (iv) many other objects and scenes [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation